Analisis Penentuan Tarif Layanan Bus Kota Berdasarkan Marginal Cost Pricing (Studi Pada Perum Damri Kota Surabaya) - Dewi Prastiwi; Dhiah Fitrayati (AKRUAL: JURNAL AKUNTANSI, 2013)
AbstractThe concept of regional autonomy has implications for financing in all sectors, including transport. To be able to provide adequate public transport facilities, one of the opportunities is the mobilization of funds through tariff collection mechanism. Determination of transport rates set out in the local rules based approach Incrementalism and line items. This approach represents a lack of economic and psychological capabilities and suitability of the benefits received by the sacrifices that have been issued. Therefore research is needed to analyze the determination of rates of local regulations bound public services locally. This study aimed to analyze the determination of the city bus rate by Cost Pricing (MCP) marginal approach, that was the determination of tariff by considering the social benefits received by customers, so if there were additional rates so consumers should receive additional social benefits. Based MCP, Perum Damri can assign the same rate if the consumer gets the same standard of service, but if there was a decline in the standard of service, then the rates should be differentiated.